A Study of Subtitling in the American Version of Zhen Huan Zhuan, Empresses in the Palace - Cao, Ziyi (Journal of Social Science and Humanities, 2025)
Under the background of economic globalization, Chinese film and television works, as an important part of cultural soft power, play an increasingly important role in cross-cultural communication. As a pivotal element in cross-cultural communication, subtitle translation for film and television dramas must effectively convey the source text to the target audience within the constraints of time and space, ensuring that viewers can accurately decode narrative information and achieve cognitive synchronization. Taking Newmark’s communicative translation theory and semantic translation theory as the theoretical framework, this study adopts the case study method and takes the subtitle translation of the American version of Zhen Huan Zhuan (甄嬛传) as the object of study, especially the translation of the title and the translation of the cultural-exclusive items. It explores whether the translation achieves a balance between cultural fidelity and audience reception. This study not only helps to deepen the understanding of the compensation strategy of cultural default in film and television translation, but also provides a practical paradigm for the translation for foreign dissemination of Chinese classical film and television works.